The Influence of International Tax Policy on the Indonesian Tax Law - Putri Anggia (Yuridika, 2019)
By 2012, the Indonesia government had validated Law Number 9 of 2017. One of the content is finance information government access to the customer bank and to the taxpayer. The government has considerations. First of all, Government will be open the access limitation of banking automatically that is necessary for taxation. The second, Indonesia has committed to international agreements of taxation which is obliged to fulfill the commitment. The commitment is to participate in implementing Automatic Exchange of Account Information (AEOI). Based on the policy, several managements and flow process around the banking area changed. Moreover as the customer bank are affected. The registration for the customer bank have been starting since 2018. By the earlier 2019, the progress of the administration needed to be checked and to be evaluated. This paper tries to discuss this issue based on the academic point of view. Data were obtained through library research. The library research was done by documentary study by collecting and analyzing selected laws and regulations, books, articles, journals and other documents which were relevant to the research. All datas were analyzed qualitavely. The implication of this research brings up a new idea about the theory of bank secrets. Initially, it is consisted of two theories, namely are absolute and relative. Despite of the two, there is a big affect in theory and academic knowledge about the validation of the agreement Indonesia government.